ANALISIS KEPUTUSAN MASYARAKAT NON-MUSLIM MENGGUNAKAN PEMBIAYAAN MURABAHAH PADA PT. BANK SUMUT KCP SYARIAH - Nadila Putri; Jon Kenedi (Adisam Publisher, 2025)
Sharia financial institutions which are part of the Indonesian community whose population is not only made up of Muslims. In its development in Indonesia, it should be appreciated because it is able to attract the interest of both Muslim and non-Muslim communities to use its products. This research aims to determine the decision of non-Muslim communities to use murabahah financing products at PT Bank Sumut KCP Syariah Rantauprapat. Interview data was used in this research with a qualitative descriptive methodology. Interviews with Bank Sumut KCP sharia staff members and non-Muslim customers were used to collect data. Research findings show that the practice of murabahah financing at PT Bank Sumut KCP Syariah Rantauprapat has received a positive view of the product. Non- Muslim communities make decisions about these products because they have factors, these factors are needs, price, type of goods, family and work environment. These factors encourage non-Muslim communities to make decisions regarding the use of murabahah financing products at PT. Bank Sumut KCP Syariah Rantauprapat